Living on the edge : an American generation's journey through the twentieth century /: an American generation's journey through the twentieth century. (2021) - Jr, Settersten, Richard A, 1964-; Jr, Elder, Glen H; Pearce, Lisa D (Lisa Deanne), 1971-
No abstract available